Respuesta :

Answer: Yes (2,-1) is the solution for those systems.

becausee...

1. 3(2) - (-1) = 7

     6 + 1 = 7

     7 = 7

2. 2(2) + 3(-1) = 1

      4 - 3 = 1

      1 = 1

Hope this helps :)

Answer:

Yes the point (2,-1) is a solution of the system: 3x - y = 7 2x + 3y = 1

Step-by-step explanation:

(2,-1) = x = 2, y = -1

Now lets put these values in the given expressions

3x - y = 7

3 × 2 - (-1)

6 + 1

= 7 THIS EQUATION IS THE SOLUTION

2x + 3y = 1

2 × 2 + 3 × (-1)

4 - 3

= 1 THIS EQUATION IS THE SOLUTION